Melanocortin 4 receptor (Mc4r) gene polymorphism and its association with body weights of some breeds of rabbit. (2020)
In livestock production, traditional methods o f selection have always been the way to go.However, with the advent o f genomics techniques, methods such as PCR-RFLP is been employed to identify single nucleotide polymorphism o f likely candidate genes useful for livestock selection and improvement. Therefore, the aim o f this study was to investigate the association o f Melanocortin 4 Receptor (MC4R) gene polymorphism with the body weight of rabbits. Seventy-four rabbits were usedfor this study consisting o f six breeds; 26 Chinchilla, 3 Californian, 11 Dutch, 4 English Spot, 10 New Zealand White and 20 Fauve de Bourgogne (FDB) breeds. Blood samples were collectedfrom the animals with needle and syringe and transferred unto FTA cards and stored away from light. Body weight measurements on the animals were recorded from 2 weeks to 20 weeks. PCR-RFLP analysis produced three genotypes AA, AG, GG with genotype frequency o f 0.14, 0.69 and 0.18 respectively. Allele frequency 0.48 and 0.52 fo r allele A and G respectively was obtained. Chi-square test showed that the population was not in Hardy-Weinberg equilibrium. Association analysis between the MC4R “c.101G>A” SNP and body weight o f rabbit was tested using GLM procedure of SAS programme. Genotype GG had higher body weight (p<0.05) at 12, 16 and 20 weeks in the Dutch rabbits while genotype AA recorded a higher (p<0.05) body weight value at 12 weeks in New Zealand White rabbits. More so, female Dutch rabbits had higher (p<0.05) mean weight than the males at 12, 16 and 20 weeks o f age. Male New Zealand White breeds recorded higher (p<0.05) mean weight than the female animals. The result of the study showed that MC4R “c.101G>A” SNP was not associated with the body weight in the studied rabbit population, although, genotype AA had higher mean weight values at 12, 16 and 20 weeks o f age than genotypes AG and GG.